Contraceptives and the Youth: Examining the Social Meaning of Contraceptives among Undergraduates in Kenya (Journal of Advanced Research in Social Sciences, 2022)
Sexuality is a development milestone in one’s life cycle, and each generation has its own struggles with it. It becomes more complex when the biological forces that accompany it initiate the sexual maturation process. The youth are very prone to risky sexual behaviour at this stage due to their perceptions of personal invulnerability, that leaves many exposed to HIV/AIDS infection, early pregnancies and abortion incidences. The unmet need for contraceptive use in sub-Saharan Africa has left the youth exposed to the aforementioned vices, making this a matter of great public health concern. Through a qualitative approach, this article examines the social meaning that the youth bestowed on two contraceptives (condom and the E-pill) and assesses how these meanings influence their sexual behaviour. The study concludes that there is need for policy makers to understand youth perceptions towards various contraceptive methods if effective campaign on reproductive health is to be realised.